Association between Maternal Factors, Preterm Birth, and Low Birth Weight of Chilean Singletons - Alejandra Rodríguez-Fernández; Marcela Ruíz-De la Fuente; Ximena Sanhueza-Riquelme; Julio Parra-Flores; María Dolores Marrodán; Eduard Maury-Sintjago (MDPI AG, 2022)
There has been an increase in preterm (PT) births in Western countries in recent years, which is associated with low-birthweight (LBW) children. The aim of this study was to determine the association between maternal factors and PT and LBW Chilean newborns. Methods: This was an analytical cross-sectional study of a national sample of 903,847 newborns and their mothers. The newborn gestational age, birth weight, maternal age, marital status, education, employment situation, and residence were analyzed. A multivariate logistic regression model was applied (α = 0.05) (STATA v.15). The prevalence was 6.8% and 5.0% for PT and LBW, respectively. The probability of the newborns being PT and LBW was 1.18 and 1.22 times if their mothers had <12 years of education and 1.38 and 1.29 times if the mothers were ≥35 years old, respectively. Mothers with <12 years education and ≥35 years were risk factors for PT and LBW newborns. Maternal educational attainment was a protective factor for the Chilean newborns, and a maternal age ≥35 years was a risk factor for PT and LBW.